Equality of Men and Women in the Perspective of Islamic Marriage Law and Article 16 of the Universal Declaration of Human Rights - Lis Diana Ningsih (al-Afkar, Journal For Islamic Studies, 2025)
This research is motivated by the fact that gender inequality in marriage is still an important issue in various countries, including from the perspective of Islamic marriage law and the provisions of Article 16 of the Universal Declaration of Human Rights (UDHR). This research aims to analyse how the principles of gender equality are applied in Islamic marriage law and Article 16 of the UDHR, and to assess their relevance and implementation in the modern legal context. This research adopts a normative legal approach with a descriptive-analytical method. Data was collected through document studies, including analysis of legal literature, legislation and international conventions, and then analysed using qualitative data analysis techniques. The results of the study show that both Islamic Marriage Law and Article 16 of the UDHR contain principles of gender equality, although there are differences in interpretation and implementation that are influenced by local culture and legal systems. The findings of this study suggest the need for harmonisation between religious norms and human rights principles to support the realisation of gender equality in marriage law.